Globalization and the market for high‐ability managers. (March 2014) - Davidson, Carl; Matusz, Steven J.
Abstract We add heterogeneous workers and search‐generated unemployment to a Melitz‐style economy. Depending on their productivity, firms choose to search exclusively for one of two types of skilled workers, or possibly undertake a broad search for either. Increased globalization changes the cost–benefit calculus of different search strategies and therefore alters the range of firms willing to implement the alternative search strategies.